2014
DOI: 10.1161/atvbaha.114.303715
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin Activates ATP-Binding Cassette Transporter A1–Dependent Efflux Ex Vivo and Promotes Reverse Cholesterol Transport in Macrophage Cells in Mice Fed a High-Fat Diet

Abstract: Objective— It is controversial whether statins improve high-density lipoprotein (HDL) function, which plays an important role in reverse cholesterol transport in vivo. The aim of the present study was to clarify the effects of rosuvastatin and atorvastatin on reverse cholesterol transport in macrophage cells in vivo and their underlying mechanisms. Approach and Results— Male C57BL mice were divided into 3 groups (rosuvastatin, atorvastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Various studies have reported different effects of treatment with statins, including rosuvastatin, on plasma and lipoprotein cholesterol levels in apoE −/− and other mice. 6 10 , 12 , 17 23 , 64 For example, some reported reductions in plasma cholesterol levels, 7 , 8 , 64 whereas others reported unaltered plasma cholesterol and triglyceride levels 6 , 9 , 10 , 12 , 17 20 , 65 , 66 in apoE −/− and other mice treated with rosuvastatin. Still other studies reported that treatment of apoE −/− mice with other statins, including simvastatin, resulted in increased plasma cholesterol levels, in some cases accompanied by increased atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported different effects of treatment with statins, including rosuvastatin, on plasma and lipoprotein cholesterol levels in apoE −/− and other mice. 6 10 , 12 , 17 23 , 64 For example, some reported reductions in plasma cholesterol levels, 7 , 8 , 64 whereas others reported unaltered plasma cholesterol and triglyceride levels 6 , 9 , 10 , 12 , 17 20 , 65 , 66 in apoE −/− and other mice treated with rosuvastatin. Still other studies reported that treatment of apoE −/− mice with other statins, including simvastatin, resulted in increased plasma cholesterol levels, in some cases accompanied by increased atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“… 14 16 Several studies demonstrated that rosuvastatin treatment at varying doses reduced inflammation, thrombosis, and apoptosis in the aortic sinus and proximal aortas of apoE −/− mice, although plasma total cholesterol and triglyceride levels were not altered. 6 , 9 , 10 , 12 , 17 20 On the other hand, other studies reported beneficial effects of rosuvastatin were accompanied by reductions in plasma total cholesterol in apoE −/− mice. 7 , 8 Still, other studies have reported that treatment of apoE −/− mice with other statins, including simvastatin, resulted in increased plasma cholesterol levels in some cases accompanied by increased atherosclerosis.…”
mentioning
confidence: 99%
“…In mouse studies rosuvastatin treatment enhanced ABCA1-specific cholesterol efflux capacity, but atorvastatin had no effect. 29 A small study showed that pitavastatin increased cholesterol efflux capacity from human macrophages by 8.6%. 30 In the JUPITER trial (Justification for the Use of Statins in Primary Prevention: An Intervention Trial Evaluating Rosuvastatin), rosuvastatin treatment increased HDL-C by 6%.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this technique can separate charge based LDL subfractions in (fast, slow and minor) with a drop of plasma and within minutes [84] . This technique is reported in CAD clinical trial testing drugs that raise HDL-C levels [85] , [86] , or in evaluating mechanism of apoA-I mimetic peptides in plasma [87] , [88] or also in some clinical laboratories as routine analytical assay [82] . Importantly, in patient with hypercholesterolemia the charge-modified LDL subfraction as determined by cITP (fLDL) subfraction is suggested as a possible potential useful biomarker for the risk of CAD [89] .…”
Section: Methods Of Hdl Measurementmentioning
confidence: 99%